2014
DOI: 10.1007/jhep09(2014)055
|View full text |Cite
|
Sign up to set email alerts
|

Higher form gauge fields and their nonassociative symmetry algebras

Abstract: We show that geometric theories with p-form gauge fields have a nonassociative symmetry structure, extending an underlying Lie algebra. This nonassociativity is controlled by the same Chevalley-Eilenberg cohomology that classifies free differential algebras, p-form generalizations of Cartan-Maurer equations. A possible relation with flux backgrounds of closed string theory is pointed out.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…This 3-cocycle provides the twisting of the pertinent horizontal product of the Lie 2-group, which was calculated explicitly for the case of toroidal backgrounds using the Baker-Campbell-Hausdorff formula. At the algebraic level, this 3-cocycle is exactly the one that appeared recently in [11], where R-space nonassociativity was similarly characterised in terms of 3-cocycles of the abelian group of translations in phase space with and without central extension using the deformation theory of Lie algebras (see also [22]).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…This 3-cocycle provides the twisting of the pertinent horizontal product of the Lie 2-group, which was calculated explicitly for the case of toroidal backgrounds using the Baker-Campbell-Hausdorff formula. At the algebraic level, this 3-cocycle is exactly the one that appeared recently in [11], where R-space nonassociativity was similarly characterised in terms of 3-cocycles of the abelian group of translations in phase space with and without central extension using the deformation theory of Lie algebras (see also [22]).…”
Section: Introductionmentioning
confidence: 69%
“…22) respectively, where R IJK := ∂ K Θ IJ is constant and non-zero (and then equal to R ijk ) only for (selected) configuration space coordinates, c.f. (3.34) and (3.27).…”
mentioning
confidence: 99%
“…This non‐associative algebraic structure was further analyzed in refs. in terms of 3‐cocycles, star‐products, tri‐products and related physics topics such as membrane sigma‐models, magnetic monopole backgrounds, and their quantization.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was found that closed strings on non‐geometric flux backgrounds have surprising features in that they exhibit non‐commutativity and non‐associativity among the closed string coordinates and their momenta . These new algebraic structures were investigated further in a subsequent series of papers , focusing on the derivation of the commutation relations for different string models and their mathematical interpretation. Independent studies by other authors, following a more mathematical line of thought, have also come to the conclusion that non‐commutative and non‐associative tori arise from geometric flux vacua by a sequence of T‐dualities .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that spontaneous compactness of d = 11 supergravity results in the following Einstein equation solutions (in the form of Castellani and Warner [88]- [90] ):…”
Section: High-dim Supergravity and High-dim Superrepulsionmentioning
confidence: 99%